The evolution of the UK North-South divide: Should we mind the gap? - Gilles Duranton; Vassilis Monastiriotis (EIB Papers, 2001)
Inequalities across regions in Europe are a matter of great interest to policy makers and politicians as well as members of the general public. Numerous studies have shown that income inequalities across European regions are large and persistent (Quah, 1996; Esteban, 2000). Interestingly, the decomposition of European regional inequalities into a cross-country and a within-country component shows that the former is declining, whereas the latter has risen significantly over the last 15 years (Esteban, 1999; Dunford and Smith, 2000).
Keywords: 330; Regionale Einkommensverteilung; Regionale Disparität; Bildungsertrag; Großbritannien